The miracle of theism : arguments for and against the existence of God - Mackie, J. L. (John Leslie) (New York : Clarendon Press, 1982)
In The Miracle of Theism, J.L. Mackie examines the arguments for and against the existence of God from an atheistic perspective. John Mackie is a highly respected twentieth century philosopher and along with Anthony Flew has been one of the most capable contemporary proponents of atheism. Written almost a quarter of a century ago, "The Miracle of Theism" remains a classic in the field of religious philosophy and is widely considered to be one of the best-stated arguments for atheism in print. Unfortunately, many popular works supporting the atheistic perspective come across as unduly angry and self-righteous. In contrast, Mackie's work is a much-needed breath of fresh air. One may disagree with Mackie while at the same time respecting his views
Miracles and testimony. Hume's argument : exposition ; Hume's argument : discussion -- Descartes and the idea of God. The argument of the Third Meditation : exposition ; The argument of the Third Meditation : discussion -- Ontological arguments. Descartes's proof and Kant's criticism ; Anselm's ontological proof and Gaunilo's reply ; Plantinga's ontological proof -- Berkeley's God and immaterial realism. Berkeley's theism : exposition ; Berkeley's theism : discussion -- Cosmological arguments. Contingency and sufficient reason ; The regress of causes ; Finite past time and creation ; Swinburne's inductive cosmological argument -- Moral arguments for the existence of a God. A popular line of thought ; Newman : conscience as the creative principle of religion ; Kant : God as a presupposition of morality ; Sidgwick : the duality of practical reason ; God and the objectivity of value -- The argument from consciousness -- Arguments for design. Hume's Dialogues : exposition ; Hume's Dialogues : discussion ; Swinburne's restatement -- The problem of evil. Survey of the problem ; Attempts to sidestep the problem ; The paradox of omnipotence ; The free will defence ; Digression : the nature of free will ; The free will defence : continued -- Religious experience and natural histories of religion. The varieties of religious experience ; Natural histories of religion -- Belief without reason. Pascal's wager ; William James and the will to believe ; Kierkegaard and the primacy of commitment -- Religion without belief? -- Replacements for God -- Conclusions and implications. The challenge of nihilism ; The balance of probabilities ; The moral consequences of atheism
Includes bibliographical references and index
Keywords: God -- Proof; Theism; Dieu - Existence; Théisme; God -- Proof; Theism